The library of Eusebius of Caesarea - Carriker, Andrew (Supplements to Vigiliae Christianae ;, 2003)
This work reconstructs the contents of the library in Roman Palestine of Eusebius of Caesarea (ca. 265-339) by examining Eusebius' major works. It discusses how Eusebius used his sources and then examines what works were available in the library relating to philosophical works.